Trends in functional programming : 16th International Symposium, TFP 2015, Sophia Antipolis, France, June 3-5, 2015. Revised selected papers /: 16th International Symposium, TFP 2015, Sophia Antipolis, France, June 3-5, 2015. Revised selected papers. (2016) - Unknown
No abstract available